Effects of different physical activity interventions on children with attention-deficit/hyperactivity disorder: A network meta-analysis of randomized controlled trials - Li, Dong; Wang, Deng; Cui, Wenlai; Yan, Jin; Zang, Wanli; Li, Chenmu (Frontiers in Neuroscience, 2023)
Background: Previous studies have shown that physical activity interventions positively affect core symptoms and executive functioning in children with ADHD. However, comparisons between different physical activity interventions still need to be made. This study evaluated the effects of 10 different types of physical activity on children with ADHD using different indicators by network Meta-analysis. Methods: PubMed, Embase, Web of Science, and Cochrane Library databases were searched for randomized controlled trials on the effects of physical activity interventions on children with ADHD. The search time frame was from database creation to October 2022. Two investigators independently performed literature screening, extraction, and quality assessment. Network Meta-Analysis with Stata 15.1. Results: A total of 31 studies were included, and the results showed that perceptual-motor training was the most effective in terms of motor ability and working memory (SUCRA=82.7% and 73.3%, respectively). In attention problems and cognitive flexibility, aquatic exercise was the most effective (SUCRA=80.9% and 86.6%, respectively). In social problems, horsemanship was the most effective (SUCRA=79.4%). Inhibition switching, Cognitive-motor Training was the most effective (SUCRA=83.5%). Conclusions: Our current study showed that the overall performance of water sports and perceptual-motor training was better. However, different physical activity interventions have different validity and individual differences regarding their effects on different indicators in children with ADHD. We should diagnose the different severity of symptoms exhibited by children with ADHD before physical activity interventions so that a reasonable and adequate physical activity intervention can be selected.